Prespektif Hukum Internasional Terhadap Individu Yang Tidak Memiliki Kewarganegaraan - Raissa Ramandhita; Arya Tirta Kusuma (Peneliti.net, 2023)
Citizenship is a form of identity that allows individuals to feel the meaning of ownership, rights and social obligations in the political community (state). Citizenship is also a person's membership in the control of a certain political unit (specifically: the state) which carries the right to participate in political activities. Under the social contract theory, citizenship status has implication rights and obligations. However some individuals do not have that nationality or identity. having citizenship can protect us legally, so if someone doesn't have citizenship then the state can't protect him according to UNCHR data around the end of 2021 there were 4.3 stateless individuals However the actual number is much more but it is not known because it can be assumed that there are a large number of unknown cases. The majority of stateless individuals are male and a quarter are aged